2016
DOI: 10.15761/gapm.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of three different methods of implementing the WHO surgical safety checklist in Guinea

Abstract: Objective: The World Health Organisation Surgical Safety Checklist improves surgical outcomes in resource poor settings but the best method of implementing the checklist is unknown. We aimed to evaluate three different methods of training in Guinea and evaluated the outcome at 3-6 months.Methods: A total of 13 individuals (4 surgeons, 7 anaesthetists and 2 nurses) from 6 different hospitals underwent 3 methods of training (hospital team training, hospital individual training and classroom only training). None … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…PENETRATION: 68,635 women received pre-test counseling; 63,094 (91.9%) of women were screened for HIV; Of those screened for HIV, 5550 (8.7%) were HIV positive; Of those who were HIV positive, 5433 (97%) were provided Nevarapine1. PENETRATION: 690 nurses, nurse aids, and trained birth attendants were trained to provide PMTCT in 115 facilities in 6 out of ten provinces in Cameroon44White et al [89]IPC Practices during surgeries (disinfection of equipment, decontamination of equipment, disinfection of environment)1. EDUCATE: (3 different training methods were used to promote the use of the WHO Surgical checklist—nurses were only trained in one method (the team method: an intra-professional training modality)2.…”
Section: Resultsmentioning
confidence: 99%
“…PENETRATION: 68,635 women received pre-test counseling; 63,094 (91.9%) of women were screened for HIV; Of those screened for HIV, 5550 (8.7%) were HIV positive; Of those who were HIV positive, 5433 (97%) were provided Nevarapine1. PENETRATION: 690 nurses, nurse aids, and trained birth attendants were trained to provide PMTCT in 115 facilities in 6 out of ten provinces in Cameroon44White et al [89]IPC Practices during surgeries (disinfection of equipment, decontamination of equipment, disinfection of environment)1. EDUCATE: (3 different training methods were used to promote the use of the WHO Surgical checklist—nurses were only trained in one method (the team method: an intra-professional training modality)2.…”
Section: Resultsmentioning
confidence: 99%
“…14 Since 2013, we have been creating and adapting a short-format checklist training course designed to address and overcome challenges to implementation. Our experience in Guinea in 2013 demonstrated better results with multidisciplinary training in a hospital setting rather than teaching individual anaesthetists or surgeons in a classroom and expecting them to return to their local setting and implement change 15 ; a pilot course in the Republic of Congo showed that a short 4-day course led to improved indices of surgical safety sustained at 18 months. 16 We also sought more involvement from local leadership (hospital directors and surgeons) and from the Ministry of Health aiming to use both a ‘bottom-up’ and a ‘top-down’ approach to checklist implementation.…”
Section: Programme Designmentioning
confidence: 90%
“…Mercy Ships operates the world’s largest non-governmental hospital ship, the Africa Mercy , which usually stays in a given country for ten months, providing free surgeries and training. Mercy Ships has trained single hospitals in checklist implementation in Guinea and Republic of Congo and has reported sustained results at 18 months [ 20 , 21 ]. Based on these experiences and those in two pilot hospitals in Madagascar, we developed a three-day checklist implementation course suitable for countrywide scale-up.…”
Section: Introductionmentioning
confidence: 99%